Forget me not an interactive augmented reality therapeutic application utilized as an intervention to neurodegeneration for individuals prone to early-onset Alzheimer's Disease in the Philippines - Bañares, Ten Ten Trixia A.; San Valentin, Marc (Quezon City College of Fine Arts, University of the Philippines Diliman, 2018)
Therapeutic recreation plays a vital role in an individual's health care. This nonpharmacologic treatment provides an individual opportunity for physical activity, emotional release, social stimulation and creative expression. Individuals affected Alzheimer's disease can benefit from this kind of therapeutic method, since it's effects of the disease not only progressively loses one's memory but also gravely affects the cognitive skills and executive functions of the brain, such as language, orientation, attention, concentration, abstract thinking and judgment. This insidious disease can manifest as early as the age thirty. However, cognitive decline is less prone to individuals who exercise and who challenge their intellect at work or play, this can be achieved by enhancing an individual's ability through cognitive exercise that is maintained through old age. The Philippines is challenged with the epidemic of Alzheimer's disease through preparation in necessary in order to confront this problem competently. Early detection and accurate diagnosis are crucial in chronic illness management in order to prevent the insidious disease to a state of irreversibility - however, not everyone in the Philippines is able to afford access this due to many factors. Forget me not provides a new platform and a nonpharmacological method of Alzheimer's disease rehabilitation and intervention. It is an application that acts as an aid for both cognitive and physical therapy for Alzheimer's disease through the use of various cognitive exercises through augmented reality (AR), providing a new layer to recreational therapy and give rise to the rate of the neurogenesis through exercise, exploration, enriched environments,learning and memory.These exercises are created to provide the user with a fresh and better experience when undergoing rehabilitation even while outside the hospital. The application would be implemented on a mobile and a tablet device, so users would be able to easily access it and bring it outside the home. The goal of Forget me not is not to replace the traditional rehabilitation process and tools, but rather create a portable and handheld digitally-translated equivalence to achieve the desired outcome by adding various cognitive exercises and physical benefits to the experience while aiding the user even while the user is not undergoing active rehabilitation sessions.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 85-87.
Keywords: Recreational therapy; Alzheimer's disease -- Patients -- Care; Alzheimer's disease -- Patients